A narrative exploration of the experiences of urban Black South African fathers. - Quinn, Theresa (My University, 2013)
This study aimed to explore the perceptions of the role of the father and the experiences of fatherhood among Black South African fathers residing in urban Johannesburg. It further investigated how the experience of being fathered influenced being a father. Qualitative methods were utilised in the form of a narrative analysis of semi structured interviews. The interviews and the analysis relied upon the guidelines of the psychoanalytic research interview (Cartwright, 2002) in providing a psychoanalytic lens through which to analyse the data. An in depth analysis of the interview data and process notes generated the following focal themes: pre-natal experiences, identification, reparation, the experience of being a father, the perceived role of the father, transitioning into fatherhood and the internal father. Becoming a father seemed to bring with it a host of different emotions and anxieties both within the prenatal and post natal stages. Becoming a father also seemed to cause the majority of the participants to reflect on their own childhoods and their experiences of being fathered. Fatherhood also seemed to provide the opportunity for some type of reparation with the participants own fathers through their new roles as fathers. Transitioning into fatherhood proved to be difficult for most of the participants and the loss of certain aspects of their lives such as their more carefree youth and less responsibility, was highlighted. Interesting to note is the point that although all the participants were Black males, little information regarding traditional beliefs around fathering emerged. This was thought to be due to the fact that all the participants resided in an urban area, thus the strong influence of western culture was apparent.
Keywords: Fatherhood--South Africa.; Fathers--South Africa.; Blacks--South Africa.; Urban blacks--South Africa.